Strategic Intent of Hospital Mergers and Acquisitions: Then and Now - Khan, Iqra; Wilson, Asa (Archives of Business Research, 2026)
The hospital mergers-and-acquisitions (M&A) trend is reviewed in terms of duration in and impact on US health care. This information supports an understanding of the strategic intent of M&As. Hospital mergers and acquisitions fostered the creation of integrated delivery networks to enhance competitive and volume-profit capacity. The value of this initial strategic intent is discussed in relation to today’s emerging population-community health and health status emphasis. Subsequent insights foster views about future expectations of and behaviors from the national system. M&As are projected to continue albeit with an expanded focus on population and community health services.